2016
DOI: 10.1016/j.nima.2016.05.132
|View full text |Cite
|
Sign up to set email alerts
|

Separation of scintillation and Cherenkov lights in linear alkyl benzene

Abstract: To separate scintillation and Cherenkov lights in water-based liquid scintillator detectors is a desired feature for future neutrino and proton decay researches. Linear alkyl benzene (LAB) is one important ingredient of a water-based liquid scintillator being developed. In this paper we observed a good separation of scintillation and Cherenkov lights in an LAB sample. The rising and decay times of the scintillation light of the LAB were measured to be (7.7 ± 3.0) ns and (36.6 ± 2.4) ns, respectively, while the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…This work found that the slow component of an exponential decay of the scintillation is stronger pronounced at lower temperatures. As the triplet lifetime of benzene matches this slow decay component well [21][22][23][24], this result can be seen as an indication that either more triplet states are populated or that the radiative de-excitation of those is more efficient at lower temperatures. The increased population would fit into the theory of Birks and Conte [9,25], who proposed that the energy transfer between solvent-solvent and solvent-solute molecules is mainly due to excimer formation.…”
mentioning
confidence: 66%
“…This work found that the slow component of an exponential decay of the scintillation is stronger pronounced at lower temperatures. As the triplet lifetime of benzene matches this slow decay component well [21][22][23][24], this result can be seen as an indication that either more triplet states are populated or that the radiative de-excitation of those is more efficient at lower temperatures. The increased population would fit into the theory of Birks and Conte [9,25], who proposed that the energy transfer between solvent-solvent and solvent-solute molecules is mainly due to excimer formation.…”
mentioning
confidence: 66%
“…With this detection material, Cherenkov light as a prompt component can be separated with a fast readout system. Linear alkylbenzene (LAB), as the primary component or ingredient of liquid scintillators, was studied [3], and its light yield is about 1000 photons/MeV and emission decay time is about 37 ns. Slow liquid scintillator samples with higher light yield were searched with LAB, 2,5-diphenyloxazole (PPO) and p-bis-(o-methylstyryl)-benzene (bis-MSB) combinations [4].…”
Section: Research and Design Progress Slow Liquid Scintillatormentioning
confidence: 99%
“…Additionally, the angular distribution of the Cherenkov light around the event direction distinguishes it from isotropic scintillation light. Benchtop scale experimental setups, such as in [21][22][23][24][25], use the timing and directionality to identify the Cherenkov light.…”
Section: Introductionmentioning
confidence: 99%